Investigating the Moderating Role of Trust between Social Media Capabilities and Consumer Brand Engagement Across Textile Sector of Pakistan - Sarmad, Muhammad; Ahmad, Naeem; Khan, Muhammad; Irfan, Muhammad; Atta, Hajira (International Review of Management and Marketing, 2020)
Social media has turned out to be a significant tool which reinforces both, consumer and firm to interact with each other and also modernizing the firm’s way of relationship with consumer. Based on the commitment-trust theory of relationship marketing this study investigates the social media capabilities to attain consumer brand engagement. The relationship is moderated through the rarely addressed role of trust across consumers of Pakistani textile manufactured garment products. This study is quantitative in nature and followed deductive research approach. The primary data were collected through well-structured questionnaire from 307 domestic customers. The data was analyzed through advanced statistical techniques operated under Smart-PLS and SPSS. The results disclosed that networking capability, image transferability and personal extensibility positively affects consumer brand engagement. The moderating role of trust is also established between the proposed relationships. The results are discussed and recommendations are provided to the targeted sector. The research findings are expected to be beneficial for targeted sector in particular and for other sectors in general. Keywords: Networking Capability, Personal Extensibility, Image Transferability, Trust, Consumer Brand Engagement JEL Classification: M1, M31 DOI: https://doi.org/10.32479/irmm.9894